(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Motivational and Self-regulated learning includes the learning process that involves metacognitive components, (the thought about one’s thought) strategic function (monitoring, controlling, planning and assessing personal development against a standard), and motivation to learn-self regulated learners achieve a great success in their academic engagement because they have self-control over their milieu. Many students are unable to learn English well because their teachers have failed to apply a good and useful strategy. Therefore, it is very crucial to put these factors into consideration in order to develop a good and reasonable method of teaching. If teachers are able to adopt and adapt a good strategy in teaching, the will and interest to learn will rise. For this reason, the process in learning and teaching English in the classroom is not something that should be handled with levity. When this is achieved it improves the learning morale of the students and the students are improved in their spoken English. Hence, this study has examined the efficacy of applying motivational and self-regulated learning strategy to examine its reliability among the northern Iraqi university students. The study was properly carried out with the intent of getting empirical evidence about how useful the strategy could be and how rewarding it will be if it is applied by teachers for the students of the northern Iraqi universities. The results revealed that motivational and self-regulated learning provides patterns to establish the motivation of the students and strengthen their personal, social and academic lives. As motivational and self-regulated strategy pervades through the whole classroom, excellent level of academic achievement becomes evidently in place. Furthermore, the findings illustrate the positive effect of motivational and self-regulated strategy among the learners. As the research study took place in a normal academic classroom setting, with some other information occurring and this has allowed motivational and self-regulated learning have effective influence in general, and to pervade though the whole classroom. Conclusively, the general results reveal that the use of motivational and self-regulated strategy is more effective and applicable for the University students in northern Iraq.